Respuesta :

Answer:

a4 = -3 * 4^(4-1) = -3 * 4^3 = -3*64 = -192

Step-by-step explanation:

A geometric sequence is a sequence of numbers such that the ratio of any two consecutive terms is always the same. In this case, the given sequence is -3, -12, -48, -192, -768.

To find the explicit formula for this geometric sequence, we can use the following formula:

an = a1 * r^(n-1)

where:

a1 is the first term in the sequence (-3)

an is the nth term in the sequence

r is the common ratio (the ratio between any two consecutive terms)

To find the common ratio, we can divide -12 by -3, -48 by -12, -192 by -48, and -768 by -192, and in all cases we get r = 4

Therefore, the explicit formula for this geometric sequence is:

an = -3 * 4^(n-1)

This formula can generate any term of the sequence given the value of n.

So, for example, the fourth term of the sequence, -192, can be obtained by inputting n = 4 in the explicit formula:

a4 = -3 * 4^(4-1) = -3 * 4^3 = -3*64 = -192